Dispenser eletrônico de sabão com aviso de recarga via web - Franklin, Larissa Avelino (2021)
A good hand sanitization has always been important, but after the emergence of the new coronavirus in 2019, this issue became the center of attention and it’s been increasingly debated and emphasized as a way to contain the advance of the vírus spreads. It is necessary to always keep hands sanitized after touching objects susceptible to contamination. Hence the use of soaps for this purpose, but even them can be contaminated, and because of that the National Health Surveillance Agency (ANVISA) determines the safe limits allowed for microorganisms in soaps. With this in mind, the search for a solution that reduces the risk of contamination, especially in places where the circulation of people is high, has a huge importance. Liquid soap is an option that reduces the contact of many people when compared to bar soap, which favors the accumulation of bacteria. The advance of technology enables the study of a viable solution to this problem, a prototype of an electronic soap dispenser for bathroom with a recharge warning when necessary, focus of this project. With the use of the dispenser, there is no need to touch anywhere, because only by placing the hands below the container the soap is released, in addition to favoring the logistics of places with many bathrooms, as warnings are sent when the container reaches 20% of the total capacity. Among the project's objectives are automatic triggering and release of soap by detecting the user's hands by a sensor, monitoring the soap level, sending a warning of the need for a refill when the level is low, to a device through wireless communication. For the development of the project, components such as sensors to detect presence and read the level, pump to release the liquid, activation relay, microcontroller and a power supply were used. The results obtained with the work indicated efficiency in the automatic soap release, also favoring its saving, as the pump remains activated only long enough to release the amount necessary for a hand washing. The warnings are sent to a mobile device application via Wi-Fi quickly, as well as level monitoring. The sensor used for level measurement showed errors of 38.5%, 6.5% and 4.6% for distance measurements between the liquid and the sensor, respectively of, 2 cm, 6 cm and 10 cm. Although there was a big error presented for small distances, the functionality of the project remained.